The Effect of Packaging Methods, Storage Time and the Fortification of Poultry Sausages with Fish Oil and Microencapsulated Fish Oil on Their Rheological and Water-Binding Properties - Jerzy Stangierski; Hanna Maria Baranowska; Ryszard Rezler; Krzysztof Kawecki (Molecules, 2022)
The aim of the study was to investigate how liquid fish oil and microencapsulated oil additives influenced the rheological characteristics and the dynamics of water binding in vacuum-packed (VP) and modified-atmosphere-packed (MAP) poultry sausages during 21-day storage. In contrast to the control sample, the sausages enriched with microencapsulated fish oil (MC) were characterised by the greatest ability to accumulate deformation energy. The elastic properties of all sausage variants increased significantly in the subsequent storage periods, whereas the dynamic viscosity of the samples tended to decrease. This phenomenon was confirmed by the gradual reduction of water activity (Aw) in all sausages in the subsequent storage periods. The packaging method influenced the dynamics of water binding in an oil-additive-form-dependent manner. During the storage of the VP and MAP sausages, in samples with the fish oil additive the T1 value tended to increase while the Aw decreased. The T1 value in the MAP MC sample was similar. The FO additive resulted in greater mobility of both proton fractions in the MAP samples than in the VP samples. There were inverse relationships observed in the MC samples. The NMR tests showed that the VP samples with the MC additive were slightly better quality than the other samples.